Successful Product Management Tool Box for Professional Product Management and Product Marketing - Aumayr, Klaus J. (Wiesbaden : Springer Fachmedien Wiesbaden : Imprint: Springer Gabler, 2023)
This book provides all readers who want to actively market their products with an indispensable and proven working aid. The author shows how product managers can deal with the increasingly complex tasks and requirements. Because the success of a product is decided by the buyers - and the responsible product manager. The product manager is fighting on several fronts: He has to introduce and support more and more products in less and less time with decreasing budgets. At the same time, he must coordinate a plethora of requirements from internal departments. With "Successful Product Management", Klaus J. Aumayr provides the complete tools to master these complex tasks with confidence. Case studies, charts and checklists facilitate the transfer into practice. The content Product management: Positioning, Core competencies and organization integration Product marketing: Structures, Success factor and practical tools Process-oriented product management:work process, process-oriented marketing and innovation management The author Klaus J. Aumayr is Managing Director of the management consultancy MSG, Management Systems St. Gallen. As a specialist in product management and key account management, he advises well-known companies. In addition to mechanical engineering, he studied business administration and completed an MBA at the University of Toronto.
Product management: positioning, core competencies and organizational integration -- Product marketing: structures, success factors and practical tools -- Process-oriented product management: work processes, process-oriented marketing and innovation management.
Keywords: Marketing; Management; Marketing; Management